2015
DOI: 10.1002/jhm.2352
|View full text |Cite
|
Sign up to set email alerts
|

The july effect: An analysis of never events in the nationwide inpatient sample

Abstract: BACKGROUND Prior studies examining the impact of the “July effect” on in‐hospital mortality rates have generated variable results. In 2008, the Centers for Medicare & Medicaid Services published a series of high‐cost, high‐volume, nonreimbursable hospital‐acquired complications (HACs). These events were believed to be preventable and indicate deficiencies in healthcare delivery. OBJECTIVE The present study aims to investigate the impact of July admissions on patient safety in a national sample using the HACs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 37 publications
(48 reference statements)
1
26
0
Order By: Relevance
“…Subsequent studies have been mixed. Several studies that focused on surgical procedures (eg, anterior cervical fusion, elective spine, head and neck cancer surgery) showed no effect, although another study showed an increase in hospital‐acquired complications for patients cared for in July . One of the best studies found that undesirable events were committed as frequently by fifth‐year trainees who were new to the hospital as by interns …”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have been mixed. Several studies that focused on surgical procedures (eg, anterior cervical fusion, elective spine, head and neck cancer surgery) showed no effect, although another study showed an increase in hospital‐acquired complications for patients cared for in July . One of the best studies found that undesirable events were committed as frequently by fifth‐year trainees who were new to the hospital as by interns …”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the findings of other aggregate NIS studies. 10,16 The association of reforms with increased HAC frequency may be due to multiple reasons. Increased number of informational exchanges during handoffs has been cited as a source of medical errors in multiple studies.…”
Section: Bottom Linementioning
confidence: 99%
“…15 HACs have been utilized as hospital quality outcome measures in studies. 10,11,16,17 No prior study has evaluated the national incidence of HACs before and after the institution of the 2003 ACGME duty hour limits. Each discharge was treated as an independent event due to the lack of unique patient identifiers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, which used Medicare data, rates of hospital-acquired complications were significantly higher for patients admitted in July compared with other months. 7 These worrisome trends are not confined to any single nation. In an international study, rates of fatal medication errors increased by 10% during the month of July in countries with teaching hospitals.…”
mentioning
confidence: 98%